A Virtual Reality Meditative Intervention Modulates Pain and the Pain Neuromatrix in Patients with Opioid Use Disorder. Issue 11 (6th May 2021) - Faraj, Mohammed M; Lipanski, Nina M; Morales, Austin; Goldberg, Elimelech; Bluth, Martin H; Marusak, Hilary A; Greenwald, Mark K
Abstract: Objective: Standard of care for opioid use disorder (OUD) includes medication and counseling. However, there is an unmet need for complementary approaches to treat OUD patients coping with pain; furthermore, few studies have probed neurobiological features of pain or its management during OUD treatment. This preliminary study examines neurobiological and behavioral effects of a virtual reality-based meditative intervention in patients undergoing methadone maintenance treatment (MMT). Design: Prospective, non-blinded, single-arm, 12-week intervention with standardized assessments. Setting: Academic research laboratory affiliated with an on-site MMT clinic. Methods: Fifteen (11 female) MMT patients completed a virtual reality, therapist-guided meditative intervention that included breathing and relaxation exercisessessions were scheduled twice weekly. Assessments included functional magnetic resonance imaging (fMRI) of pain neuromatrix activation and connectivity (pre- and post-intervention), saliva cortisol and C-reactive protein (CRP) at baseline and weeks 4, 8 and 12; and self-reported pain and affective symptoms before and after each intervention session. Results: After each intervention session (relative to pre-session), ratings of pain, opioid craving, anxiety and depression (but not anger) decreased. Saliva cortisol (but not CRP) levels decreased from pre- to post-session. From pre- to post-intervention fMRI assessments, pain task-related left postcentral gyrus (PCG) activation decreased. At baseline, PCG showed positive connectivity with other regions of the pain neuromatrix, but this pattern changed post-intervention. Conclusions: These preliminary findings demonstrate feasibility, therapeutic promise, and brain basis of a meditative intervention for OUD patients undergoing MMT.